2019
DOI: 10.3390/pr7050311
|View full text |Cite
|
Sign up to set email alerts
|

Aeration Process in Bioreactors as the Main Energy Consumer in a Wastewater Treatment Plant. Review of Solutions and Methods of Process Optimization

Abstract: Due to the key role of the biological decomposition process of organic compounds in wastewater treatment, a very important thing is appropriate aeration of activated sludge, because microorganisms have to be supplied with an appropriate amount of oxygen. Aeration is one of the most energy-consuming processes in the conventional activated sludge systems of wastewater treatment technology (may consume from 50% to 90% of electricity used by a plant), which makes it the most cost-generating process incurred by tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 64 publications
(94 reference statements)
1
72
0
Order By: Relevance
“…This approach drew on the concept, suggested Maruéjouls et al [47], that PSVD is a determining factor for the prediction of the wastewater quality along a catchment, a combined sewer, or a primary treatment system. This research, as well as studies conducted by other authors [47,[51][52][53][54][55]57], confirms that a comparative study of the original and modified ASM2d models that accounts the effects of the COD fraction and particles sizes of molecules on the hydrolysis process should be applied under transient conditions (summer, spring and winter). The distribution data were fed into the hydrolysis model that involved a comparison of results on the wastewater quality that were obtained in the course of simulations that were performed at the hydrolysis rates of particles (such as molecules size and forms of COD substrates) that depended on the OUR batch tests as well as the conditions of the settling velocities ( Figure 5).…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fosupporting
confidence: 83%
See 1 more Smart Citation
“…This approach drew on the concept, suggested Maruéjouls et al [47], that PSVD is a determining factor for the prediction of the wastewater quality along a catchment, a combined sewer, or a primary treatment system. This research, as well as studies conducted by other authors [47,[51][52][53][54][55]57], confirms that a comparative study of the original and modified ASM2d models that accounts the effects of the COD fraction and particles sizes of molecules on the hydrolysis process should be applied under transient conditions (summer, spring and winter). The distribution data were fed into the hydrolysis model that involved a comparison of results on the wastewater quality that were obtained in the course of simulations that were performed at the hydrolysis rates of particles (such as molecules size and forms of COD substrates) that depended on the OUR batch tests as well as the conditions of the settling velocities ( Figure 5).…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fosupporting
confidence: 83%
“…For example, the experiments that were performed in [56] showed that when wastewater flows from an urban catchment to the biological treatment, the particle settling velocity distribution (PSVD) becomes highly differentiated. Moreover, this study showed that the model enables the reproduction of the dynamic PSVD evolution of wastewater while the suspended solids flow through the integrated urban wastewater system, which comprises an urban catchment, a combined sewer, retention tanks, a grit chamber, and a primary clarifier under dry and wet weather conditions [57,58]. Maruéjouls et al [47] also discussed an original concept that linked PSVD with hydrolysis rates, as well as the influence of ASM model parameters on the quality of the effluent.…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fomentioning
confidence: 98%
“…A brief search of their energy consumption is carried out, and it was found that systematic analyses of equipment consumption are rarely reported in the available literature [19]. An exception to this is, for example, Drewnowski et al [20], who lists the average consumptions of individual processing units in Polish WWTPs, or a study from 1994 evaluating the operating costs of all wastewater treatment plants in the province of Ontario (Canada) [21]. In their work, they found that many factors influenced the energy consumption of individual plants, in particular the overall size of the plant, the size and design of the respective equipment, the condition of the equipment, etc.…”
Section: Selection Of Equipment For a Reviewmentioning
confidence: 99%
“…In addition, other sources mention the consumption of pumping but only as total value. In Poland, the pump consumption ratio is 18% [20]; in the U.S., it is 14.8% [23]; in Ontario, Canada, 21.1% [21]; and in China, 17.8% [24].…”
Section: Selection Of Equipment For a Reviewmentioning
confidence: 99%
“…The first part of this Special Issue consists of 46 works (41 research articles; 3 review papers, 1 teaching note; 1 project report) from distinguished authors worldwide . Among them, there are several processes of wastewater treatment including major techniques as adsorption [2,3,6,7,14,15,20,25,31,36,38,40,45], membranes/filtration [8, 35,37,43,44], floation/flocculation/coagulation [11,18,26,46], ultrasonication/ozonation/aeriation [13,23], electroprocesses [1, 22,33], photocatalysis [34], etc. Many authors, whom we-as editors-thank very much, from various countries, contributed marvellously to this first part of the present Special Issue.…”
mentioning
confidence: 99%